Politik dan Pendidikan Nahdlatul Ulama - Nur Rohmah Hayati (LPPM IAINU Kebumen, 2019)
In the midst of world changes that are happening, NU needs to see opportunities and challenges. The biggest challenge is the free market that is currently attacking Indonesia, in various forms, however the world order is no longer uni polar but is starting to tend to be multipolar. Many of these opportunities and challenges were taken advantage of think NU and many say internally NU is only capable sending people in the cabinet to fill religious positions, but in the presidential era Jokowi NU is getting more attention because there are. A line of NU ministers in the Era President Jokowi. The awareness that NU has experienced stagnation can endanger NU's journey and its existence in the future, NU needs to make efforts reforms include: First, in terms of the implementation system education that only relies on studies that are sourced from studies traditional books must be adapted to the demands of the modernization paradigm. Second, from the management side, starting from the pesantren to the organization, because according to the groupprogressive groups of traditional groups can be defeated by a large number of groups small with good management. Third, NU cannot have contact with the outside world avoided again in defensive ways, but instead should be seen as objective conditions that must be faced by making various adjustment efforts within NU itself.